Trust in Coworkers and Trust in Organizations - TAN, Hwee Hoon (Institutional Knowledge at Singapore Management University, 2009)
The authors proposed a modified model of organizational trust that incorporates trust in 2 foci: coworkers and organizations. They found a relation between the 2 foci. The authors also found that trust in organizations mediates the relation between trust in coworkers and organizational outcomes of affective commitment and performance. These findings suggest that it would be meaningful to examine the relations between other foci of trust to better understand how different domains interact and how such exchanges eventually lead to desired organizational outcomes.